2002
DOI: 10.2337/diabetes.51.2.347
|View full text |Cite
|
Sign up to set email alerts
|

A Metalloporphyrin-Based Superoxide Dismutase Mimic Inhibits Adoptive Transfer of Autoimmune Diabetes by a Diabetogenic T-Cell Clone

Abstract: We present here the first report of a metalloporphyrinbased antioxidant that can prevent or delay the onset of autoimmune diabetes. Type 1 diabetes is an autoimmune process whereby T-cells recognize pancreatic ␤-cell antigens and initiate a leukocyte infiltrate that produces proinflammatory cytokines and reactive oxygen species (ROS), ultimately leading to ␤-cell destruction. Because islet ␤-cells have a reduced capacity to scavenge free radicals, they are very sensitive to ROS action. Metalloporphyrin-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 83 publications
10
152
0
1
Order By: Relevance
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 55%
“…In all previous studies the data obtained with E. coli parallel the trends obtained in in vivo animal model studies [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]37]. Here we compare the effect of Mn II Br 8 TM-3-PyP 4+ , its metal-free porphyrin HBr 8 TM-3-PyP 3+ , and the para analogue Mn II Br 8 TM-4-PyP 4+ on the aerobic growth of an SOD-deficient E. coli strain.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colimentioning
confidence: 63%
“…An essential role for ROI in T cell function was initially demonstrated by reports indicating that antioxidants inhibit proliferation and IL-2 production when administered during the early stages of T cell activation (17,18). Subsequent in vivo studies found that antioxidant treatment of mice decreased the proliferation and cytokine production of Ag-specific T cells in both autoimmune and infectious models (19,20). These findings suggest that ROI generated in response to receptor stimulation act as positive mediators involved in lymphocyte activation.…”
mentioning
confidence: 98%
“…[112][113][114][115][116][117] Some of these antiapoptotic proteins fused to protein-transduction domains can successfully prevent apoptosis and significantly improve islet yield and survival following isolation. 30,118,119 We and others have also shown that the inclusion of synthetic mimetics of free-radical scavengers seem to prevent islet degeneration possibly limiting the initiation of apoptotic processes. 105,119 Islets also take up oligonucleotides quite efficiently (unpublished observations).…”
Section: Insulin Replacement Strategiesmentioning
confidence: 96%
“…30,118,119 We and others have also shown that the inclusion of synthetic mimetics of free-radical scavengers seem to prevent islet degeneration possibly limiting the initiation of apoptotic processes. 105,119 Islets also take up oligonucleotides quite efficiently (unpublished observations). Knowledge of the primary transcripts whose protein products are involved in apoptosis activation or suppression of insulin production can be targeted with antisense oligonucleotides during the isolation procedure.…”
Section: Insulin Replacement Strategiesmentioning
confidence: 96%